2017
DOI: 10.1002/pmic.201600407
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Prenatal Iron Deficiency and Risperidone Treatment on the Rat Frontal Cortex:  A Proteomic Analysis

Abstract: Prenatal iron deficiency (pID) has been described to increase the risk for neurodevelopmental disorders such as autism and schizophrenia; however, the precise molecular mechanisms are still unknown. Here, we utilized high-throughput MS to examine the proteomic effects of pID in adulthood on the rat frontal cortex area (FCA). In addition, the FCA proteome was examined in adulthood following risperidone treatment in adolescence to see if these effects could be prevented. We identified 1501 proteins of which 100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 71 publications
(75 reference statements)
0
5
0
Order By: Relevance
“…Thus, the stellar subtype might be the cell type most likely to survive an insult than the other two OL subtypes. Recently, we have also found altered expression of proteins involved in metabolic processes including tricarboxylic acid (TCA) cycle and mitochondrial dysfunction in dID (Farrelly et al, ). These findings were associated with decreased expression of CNPase, PLP, MAG, MOG, and MBP, supporting the requirement of iron for optimal OL function and myelin synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the stellar subtype might be the cell type most likely to survive an insult than the other two OL subtypes. Recently, we have also found altered expression of proteins involved in metabolic processes including tricarboxylic acid (TCA) cycle and mitochondrial dysfunction in dID (Farrelly et al, ). These findings were associated with decreased expression of CNPase, PLP, MAG, MOG, and MBP, supporting the requirement of iron for optimal OL function and myelin synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…C-WT, WT mice on a control diet; dID-WT, WT mice on an iron-deficient diet [Color figure can be viewed at wileyonlinelibrary.com] ID is one of the most important nutritional deficits, affecting almost 2 billion people worldwide. Maternal ID during gestation has been associated with important offspring neurological impairment, including motor and social neurological dysfunction (Bakoyiannis et al, 2015;Farrelly et al, 2017). When acquired during development, ID impacts OL maturation, which causes long-lasting hypomyelination in adulthood even after an iron-sufficient diet has been reinstated (Badaracco et al, 2008;Ortiz et al, 2004).…”
Section: Behavioral Correlation With Didmentioning
confidence: 99%
“…Abnormalities in hippocampal energy metabolism have been documented in ID rats in adulthood, long after iron repletion (Carlson et al, 2007;de Deungria et al, 2000). Previous studies by our lab using labelfree liquid chromatography-tandem mass spectrometry (LC-MS/ MS) (Farrelly et al, 2017) et al, 2023). Most interestingly, given its location on the outer mitochondrial membrane, it has been speculated that DMT1 may participate in iron uptake in mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormalities in hippocampal energy metabolism have been documented in ID rats in adulthood, long after iron repletion (Carlson et al., 2007; de Deungria et al., 2000). Previous studies by our lab using label‐free liquid chromatography–tandem mass spectrometry (LC–MS/MS) (Farrelly et al., 2017) have demonstrated a pattern of dysregulated proteins involved in mitochondrial bioenergetics, the TCA cycle, and Akt signaling following prenatal ID. We have also recently demonstrated that ID OLG and AST obtained from a gestational ID model exhibit decreased spare respiratory capacity, which induces mitochondrial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Optimized methods provided good peak capacity with a 1D-LC method that was preferred over 2D-LC given the sample limitations working with the small orbital subdomain of the juvenile rat PFC, while still providing sufficient neuroproteome coverage. Across biological replicates, 2,067 proteins were identified from 20,504 reproducibly measured peptides in the OFC, which represented 38-66% greater neuroproteome coverage over recent proteomic studies in adult rat whole PFC or OFC [2527] . Precisely 800 proteins (37.5%) were significantly responsive to juvenile ETS exposure at a 5% FDR (Table 1, Supporting Information), with 716 increased and 84 decreased (Figure 1A).…”
mentioning
confidence: 99%